Implications of the Foucauldian decentralization of economics - Zulfiqar Ali (The Journal of Philosophical Economics, 2011)
This essay aims to explore Foucault’s project of decentralizing economics and to hint on some implications. It also makes a comparative analysis between Foucault’s project and the projects similar to his design and aim. I argue that Foucault’s critique of the idea of economics as a science is stronger than that of the critiques which challenge the status of economics as a science by exposing its deep fictional, literary or narrative content and style. I argue that the strength of Foucault’s decentralization project lies in the fact that he does not refer to the discursive content of economics in order to demonstrate that it is not a science. Instead, he unveils its epistemological conditions the character of which deeply haunts the sketch of economics as a science. Foucault undertakes decentralization both at the formal and historical level. At the formal level he shows that there are underlying epistemological conditions that govern the formation of discourses including economics in the West. At the historical level he demonstrates that there is no trace of economics up to the eighteenth century in the West. This fact, that economics is governed by modern Western epistemological conditions, encourages me to question the aim of teaching economics in societies such as Pakistan which are not part of the Western civilization.